Culture and the prevalence of hallucinations in schizophrenia - Bauer, Susanne M.; Schanda, Hans; Karakula, Hanna; Olajossy-Hilkesberger, Luiza; Rudaleviciene, Palmira; Okribelashvili, Nino; Chaudhry, Haroon R.; Idemudia, Sunday E.; Gscheider, Sharon; Ritter, Kristina; Stompe, Thomas (Comprehensive psychiatry, 2011)
Besides demographic, clinical, familial, and biographical factors, culture and ethnicity may plausibly influence the manifestation of hallucinations. The purpose of this study was to investigate the influence of culture on the frequency of different kinds of hallucinations in schizophrenia. Patients with a clinical diagnosis of schizophrenia were diagnosed by means of the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition criteria. Seven independent samples were consecutively recruited in Austria, Lithuania, Poland, Georgia, Ghana, Nigeria, and Pakistan using identical inclusion/exclusion criteria and assessment procedures (N = 1080 patients total). The association of key demographic factors (sex and age), clinical factors (age at onset and duration of illness), and country of origin with hallucinations of different kinds was examined. The prevalence of various kinds of hallucinations was substantially different in the samples; however, the rank order of their occurrence was similar. Auditory hallucinations were relatively infrequent in Austria and Georgia and more prevalent in patients with an early age at onset of disease. Visual hallucinations were more frequently reported by the West African patients compared with subjects from the other 5 countries. Cenesthetic hallucinations were most prevalent in Ghana and in patients with a long duration of illness. We hypothesize that the prevalence of the different kinds of hallucinations in schizophrenia is the result of the interaction of a variety of factors like cultural patterns as well as clinical parameters. According to our study, culture seems to play a decisive role and should be taken into account to a greater extent in considerations concerning the pathogenesis of psychotic symptoms.